2019
DOI: 10.1111/jan.14275
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analyses of randomized control trials of the effectiveness of psychosocial interventions for homeless adults

Abstract: Aims To evaluate the effect of psychosocial interventions for homeless adults on their psychosocial outcomes. Design A systematic review and meta‐analyses were performed for critical appraisal and synthesis of the included studies. Data sources A systematic search of studies published before 10 September 2018 was performed using PubMed, Cochrane Library, EMBASE, PsycINFO, and CINAHL. Review methods The review included randomized controlled trials conducting psychosocial interventions and assessing psychosocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Although substantially overlapping, we nonetheless recorded “people not experiencing homelessness” and “general population” controls, as documented by the original study at review. The included MA of RCTs controlled for various treatment exposures [ 220 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although substantially overlapping, we nonetheless recorded “people not experiencing homelessness” and “general population” controls, as documented by the original study at review. The included MA of RCTs controlled for various treatment exposures [ 220 ].…”
Section: Resultsmentioning
confidence: 99%
“…One eligible MA of intervention studies documented two therapeutic interventions, evaluated by 10 unique RCTs from 10 original reports, estimating interventions associated with mental health status among PEH [ 220 ]. One association concerned the psychological interventions among PEH diagnosed with depression, while the remaining one dealt with psychological interventions for anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Most efforts to reduce suicidal ideation and behavior among people who are homeless rely on indirect approaches to prevent suicide. These include strategies to enhance mental health through the reduction of anxiety and depression, enhancing perceived self-efficacy and empowerment [ 42 ], or through interventions such as Housing First (HF). Of course, an ongoing effort to address underlying housing insecurity and to tackle primary social determinants leading to poverty should be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence is mixed on whether HF improves the complex mental health needs of those who are homeless compared with treatment as usual. Most studies have found that although HF is an essential intervention to provide housing stability and has been shown to increase quality of life and decrease hospital stays, it does not show greater improvements in mental health scores or reduce suicidal ideation or attempts any more than treatment as usual [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses seem to play an important role in reducing anxiety as a symptom, that is, the “feeling of threat, danger or distress,” represented, for instance, on the focus and the diagnosis axes of the International Classification for Nursing Practice ® (ICNP ® ) (International Council of Nurses [ICN], 2019). Also, the efficacy and effectiveness of nursing interventions addressing anxiety have already been evaluated in several studies (e.g., Hyun et al, 2020; Sampaio et al, 2018), mostly with positive results. However, while some research has been conducted to evaluate the efficacy and effectiveness of nursing interventions addressing the nursing focus “anxiety,” no literature was identified which summarised those interventions.…”
Section: Introductionmentioning
confidence: 99%